2007
DOI: 10.1103/physreve.75.051304
|View full text |Cite
|
Sign up to set email alerts
|

Underconstrained jammed packings of nonspherical hard particles: Ellipses and ellipsoids

Abstract: Continuing on recent computational and experimental work on jammed packings of hard ellipsoids [Donev et al., Science, vol. 303,[990][991][992][993] we consider jamming in packings of smooth strictly convex nonspherical hard particles. We explain why the isocounting conjecture, which states that for large disordered jammed packings the average contact number per particle is twice the number of degrees of freedom per particle (Z = 2d f ), does not apply to nonspherical particles. We develop first-and second-ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
379
5
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(425 citation statements)
references
References 41 publications
37
379
5
4
Order By: Relevance
“…The preparation under gravity has strong influence on the particle orientations and thus on the force distributions. On the other hand, a systematic study of the shear behavior of 2D packings of rounded-cap rectangles (RCR) under homogeneous boundary conditions indicates that the shear strength increases with elongation whereas the packing fraction varies unmonotonically [22], as also found for packings of ellipsoidal shapes [20,21]. In all reported cases, the networks resulting from various shapes appear to be highly complex and hardly amenable to simple statistical modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation under gravity has strong influence on the particle orientations and thus on the force distributions. On the other hand, a systematic study of the shear behavior of 2D packings of rounded-cap rectangles (RCR) under homogeneous boundary conditions indicates that the shear strength increases with elongation whereas the packing fraction varies unmonotonically [22], as also found for packings of ellipsoidal shapes [20,21]. In all reported cases, the networks resulting from various shapes appear to be highly complex and hardly amenable to simple statistical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies of particle shape dependence in granular materials have been recently reported for polygonal/polyhedral [14][15][16][17][18], elliptical/ellipsoidal [19][20][21][22] and non-convex shapes [23]. The force chains are found to be reinforced in packings of polygonal and polyhedral particles leading to enhanced shear strength [15,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…As in an amorphous or glassy structure the lattice sites are randomly distributed and are not known, the above simplification is not possible. We can, however, calculate and have an idea of inhomogeneity and its difference from that of a crystalline solid using the distribution of R n determined from numerical simulations [20,21]. Thus…”
Section: Free-energy Functionalmentioning
confidence: 99%
“…The usual way to construct amorphous structure in experiment or numerical simulation is to compress the system according to some protocol which avoids crystallization [17,20,21]. One of the criteria used to signal the onset of glassy phase in supercooled liquids is emergence of split second peak.…”
Section: Amorphous Structurementioning
confidence: 99%
“…The dynamic methods were widely used for the ellipsoid packing and high densities were reported in published works [15][16][17][18]. For the methods in which ellipsoidal particles are generated by choosing randomly initial position and orientation and letting them fall in an open box under the gravity, an anisotropic behaviour of the packing system was reported [18,19].…”
mentioning
confidence: 99%